Digital Resistance and Representation: Media Narratives of Marginalized Groups in a Global Context - Jariah, Ainun (Indonesian Scientific Publication, 2025)
Media representations of marginalized communities significantly influence public perceptions and social inclusion. This narrative review aims to analyze how traditional and digital media construct narratives about marginalized groups, oscillating between reinforcing stereotypes and fostering empowerment. A comprehensive literature search was conducted using Scopus, Google Scholar, and EBSCOhost, focusing on studies employing keywords such as